THE USE OF DIARY WRITING IN TEACHING WRITING RECOUNT TEXT - Qarina, Cindy; Sutapa Y, Y Gatot; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMost of students? problems in writing are they haven?t know how to generate and develop the idea. They write based on what in their mind randomly without any technique that can help them to write the ideas and used their thinking skill well. To solve the problem, Diary Writing technique was applied to improve the students? skill in writing recount text. To examine the technique, a pre-experimental research was conducted in MAN 1 Pontianak with tenth grade students as the population and class X IPA 1 as the sample that consisted of 38 students. To gain the data indicating the effect of the technique used pre-test and post-test as the instruments and measurement test was used as the tool of the data collection. Based on the result of hypothesis testing as well as analysis of the effect size, it shows that use of diary writing had a strong effect in teaching writing recount text in MAN 1 Pontianak. Diary writing enabled the students to get more practices in writing and it could help them to elaborate the idea in writing. It was indicated by the improvement of students? writing achievement after getting the treatments. Therefore, this technique is recommended to be implemented in teaching writing recount text. Keywords: Diary Writing, Recount Text, Writing Achievement